Strategy to Improve Community Welfare in Tanjungjaya Tourist Village Through the Asset-Based Community Development (ABCD) Approach - Choerunisa, Siti; Ingkadijaya, Rahmat; Ratu Balqis, Linda Desafitri; Boediman, Surya Fadjar (Jurnal Toursci, 2025)
Background. Tanjungjaya Village has high tourism potential in Pandeglang Regency. Still, its community welfare remains relatively low, characterized by high unemployment rates, limited MSME involvement in the tourism sector, and fluctuating incomes. Aims. This study aims to formulate a strategy for improving community welfare in Tanjungjaya Tourism Village through an Asset-Based Community Development (ABCD) approach. This approach emphasizes community development based on local assets, including physical, human, social, economic, and environmental assets. Methods. This study used a qualitative case study method with data collection techniques including interviews, observation, and documentation. Result. The results indicate that the majority of residents work in the informal sector, such as fishermen, traders, or daily coastal workers, but have not yet received significant economic benefits from tourism activities. Through asset mapping and increasing community literacy, the ABCD strategy can help the community recognize, manage, and develop its potential independently. Conclusion. This study concludes that community empowerment through the ABCD approach can be a strategic alternative for promoting inclusive and sustainable village-level tourism management and improving equitable community welfare. Implementation. The proposed plan includes improving tourism literacy, empowering local MSMEs, establishing community-based tourism institutions, and participatory evaluation.